Tolerance of Trichoderma Atroviride (Karst.) Isolated From Freshwater Ecosystems towards Copper and Zinc - Yazdani, Mazyar (2008)
Isolation of microfungi from sediment samples of Kuyoh River Industrial Area, Kuyoh River Residential Area and Sri Serdang Lake was done on Rose Bengal Agar (RBA). The fungi were exposed to increased concentrations of Cu2+ (5 to 600 mg/L) and Zn2+ (5 to 6000 mg/L) on Potato Dextrose Agar (PDA) to find the most tolerant isolate. The highest tolerance to both elements was shown by Trichoderma atroviride. Further studies on growth rate, uptake capacity and localization of Cu2+ and Zn2+ were made by using Potato Dextrose Broth (PDB) incorporated with 25 to 300 mg/L of Cu2+ and 500 to 1000 mg/L of Zn2+. This study found that the uptake capacity of T. atroviride for Cu2+ ranged from 0.77 to 11.20 mg/g between 25 to 300 mg/L in the liquid medium while that for Zn2+ ranged from 18.1 to 26.7 mg/g between 500 to 1000 mg/L in the liquid medium. The isolate showed that 50.3 to 85.4 % adsorption and 9.6 to 47.1 % absorption for Cu2+ and 47.6 to 64% adsorption and 30.4 to 45.1% absorption for Zn2+. Based on the present studies, 2.7 to 5 % of Cu2+ and 5.7 to 7.4 % of Zn2+removal was observed due to biomass washing. The mean levels of Cu2+ in the surface sediment of the three mentioned sites were 347.64 μg/g, 32.04 μg/g and 21.71 μg/g while the mean levels of Zn2+were 219.75 μg/g, 140.64 μg/g and 85.10 μg/g, respectively. This study suggests that T. atroviride is a potential bioremediator of Cu2+ and Zn2+. However, further studies are needed to confirm its practical use as a bioremediating agent.